Relation between changes in plasma calcium in first week of life and renal function. Issue 10 (October 1975) - Stimmler, L; Snodgrass, G J; Gupta, Y; Stothers, J K; Brown, D
Abstract : (1) Of 71 infants fed on reconstituted dried or evaporated cow's milk, 31 showed a fall in plasma calcium between the 1st and 6th days of life, whereas in 35 breast-fed infants this occurred in only 5. (2) Those artificially-fed infants who had shown a rise in plasma calcium over this period had significantly lower plasma creatinine values and significantly higher excretion of creatinine than those infants who showed a fall in calcium levels. (3) Artificially-fed infants who had shown a rise in calcium had significantly lower plasma osmolality and significantly higher osmolar excretion in the urine than those infants who showed a fall in plasma calcium. (4) It is suggested that a delay in the normal increase in glomerular filtration rate during the first week of life in some infants leads to phosphate retention. This, together with a higher dietary intake of phosphate, leads to a decrease of the plasma calcium to hypocalcaemic levels.